Analisis Kesulitan yang Dihadapi Mahasiswa FKIP Biologi Universitas Abulyatama selama Pelaksanaan PPL pada Aspek Masalah Pribadi - Samsuar Samsuar; Syarifah Farissi Hamama; Syarifah Fadiya Hallaby (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This research was conducted to analyze the difficulties encountered by the prospective teacher of Biology FKIP Universitas Abulyatama during the Teaching Training Program at Personal issues. This research was a descriptive research with quantitative approach. Data collection in this study were obtained by questionnaires in the form of Likert scale. The result showed that lack of creativity was the main difficulties faced by the biology prospective teacher (67%; medium). On the other hand, being far from spouse, children and household related problems were the least encountered difficulties (28%; low) during the Teaching Training Program.